Climate change impacts population dynamics and distribution shift of moose (Alces alces) in Heilongjiang Province of China. Issue 4 (17th May 2013) - Dou, Hongliang; Jiang, Guangshun; Stott, Philip; Piao, Renzhu
Abstract: The earth is experiencing obvious climate warming, which may impact population dynamics and the distribution of moose ( Alces alces ). In this study, we examined the effects of density dependence, temperature, snow depth, and the vegetation (NDVI) on the population dynamics of moose in Heilongjiang Province of China using historical data. Our results demonstrated that moose distribution had continued to contract from the 1980s to the 1990s; moose densities and late spring temperatures in the 1980s were negatively correlated to the rate of increase of the moose population; low and high snow depths in the 1990s showed positive and negative effects, respectively, on the rate of population increase; and the effect of NDVI in the 1980s was similar to the effect of snow depth. Therefore, we confirmed that moose population dynamics is influenced both by intrinsic density‐dependent and extrinsic habitat factors, especially late spring temperatures. In addition, an increase in late spring temperatures may shift the southern limit of the distribution of the moose northwards, or may isolate the southernmost portion of the moose population because the rate of warming is higher to the north of a present latitudinal constriction in range than it is at the latitude of the southernmost moose.